Graduate Training in the Faculty of Nursing at Universidad de Antioquia. A Contribution to Society’s Needs for Care - Posada Vera , Elvigia María (Investigación y Educación en Enfermería, 2025)
Creation of graduate studies as academic programs in the Faculty of Nursing at Universidad de Antioquia began during the 1980s as a result of the generation of knowledge product of profound academic discussions in research and disciplinary areas. The Master’s, specialization, and PhD programs have generated an important academic production that helps make the Faculty visible in the world. These programs are permanently subjected to self-evaluation processes, which lead to improvement plans aimed at raising their quality in response to scientific progress, social needs, and health and education policies within the framework of graduate training for nursing professionals, which guarantees the social pertinence of their formation. Currently, the Faculty’s graduate programs are pertinent in their purpose of training professionals capable of confronting society’s heterogeneity and proposing solution alternatives according to the new challenges from the context to live with quality and dignity. This text seeks to show the historical development of graduate training in the Faculty of Nursing at Universidad de Antioquia in its 75 years of existence and its contribution to care and development of nursing in our society.